PENINGKATAN KUALITAS PELAYANAN ADMINISTRASI PERNIKAHAN DIKANTOR URUSAN AGAMA KECAMATAN PARINGIN SELATAN KABUPATEN BALANGAN - Paulina, Siti (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to determine the quality of service at the South Paringin District Religious Affairs Office. The research method used is qualitative with a qualitative descriptive research type. seen from the measurement of service quality dimensions at the South Paringin District Religious Affairs Office, it is quite good, this can be seen from: Tangible can be categorized as quite good, the Paringin District Religious Affairs Office has provided adequate service facilities. There are several facilities that are lacking, such as televisions, fans and chairs in front of KUA, Reliability can be categorized as good, seen from the ability of South Paringin KUA employees to provide services in creating the promised services accurately, quickly and responsively, Responsiveness can be categorized as quite good, seen from how the South Paringin District KUA is responsive in providing services. but they were less alert, because there were still many catin groups left standing in the queue for the wedding ceremony. Assurace could be categorized as good and